PERAN PENDIDIKAN DALAM KELUARGA KRISTEN - Purba, Asmat; Sihombing, Daniel Romi (Jurnal TEDC, 2024)
Everything starts with the family. Children are born and raised and educated by both parents. The results of family education will be seen directly in the lives of children in the period of growth until they are adults. What parents sow to children, that is what will be harvested from them. As the saying goes: "fruit falls not far from the tree," meaning what parents play and what is taught, that is what children imitate and live by. Children are God's entrustment to the family so that they are well educated according to the teachings of God's words. Parents perform a number of roles such as priest, father and mother, teacher of all subject areas, counselor, companion and so on. Parents not only meet the inner sustenance of the children but the overall needs of the child must be prepared by both parents. Keywords: role of parents, children, education, Christianity